1974
DOI: 10.1021/jm00248a004
|View full text |Cite
|
Sign up to set email alerts
|

Potential psychotomimetics. 2. Rigid analogs of 2,5-dimethoxy-4-methylphenylisopropylamine (DOM, STP)

Abstract: 2-Amino-5,8-dimethoxy-6-methyl-l,2,3,4-tetrahydronaphthalene and 2-amino-4,7-dimethoxy-5-methylindan were prepared as rigid analogs of psychotomimetic phenylisopropylamines. Neither compound appeared to have psychotomimetic activity in rats. The effect of the aminotetralin derivative on 5-HT receptors in rat fundus strips and sheep umbilical arteries was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Early studies with 2-aminotetralin and indan derivatives had indicated that the side chain probably could not lie in the plane of the aromatic ring. [100][101][102] Additional evidence for the nature of the active conformation came with virtual docking of mescaline into a homology model of an in silico 'activated' model of the 5-HT 2A receptor. 103 Upon docking, it was observed that tethering the side chain back to the ring to afford an aminomethyl compound would provide a compound that closely mimicked the virtually docked conformation of mescaline.…”
Section: Attempts To Identify the 'Active' Conformation Of The Phenetmentioning
confidence: 99%
“…Early studies with 2-aminotetralin and indan derivatives had indicated that the side chain probably could not lie in the plane of the aromatic ring. [100][101][102] Additional evidence for the nature of the active conformation came with virtual docking of mescaline into a homology model of an in silico 'activated' model of the 5-HT 2A receptor. 103 Upon docking, it was observed that tethering the side chain back to the ring to afford an aminomethyl compound would provide a compound that closely mimicked the virtually docked conformation of mescaline.…”
Section: Attempts To Identify the 'Active' Conformation Of The Phenetmentioning
confidence: 99%
“…Recently the tetralin and indan analogs of MDA have been examined (figures 11 to 14). It was previously shown that when hallucinogenic amphetamine derivatives were incorporated into similar structures, the hallucinogen-like activity in animal models was lost (Nichols et al 1974). Thus.…”
Section: Side-chain Modificationsmentioning
confidence: 99%
“…[195] Both hypotheses were initially supported by SAR studies on stereochemical selectivity, and rigid DOM (15) analogues. [157,196,197] Substituted tetrahydronaphthofurans have recently been synthesized as phenylalkylamine-ergoline composite molecules designed to mimic the A, B and C ring structure of ergo- lines. [198] Pharmacological evaluation of compound 42 revealed binding affinities at […”
mentioning
confidence: 99%
“…Extending previous work on indanalkylamine analogues of DOM (15), [197] a conformationally constrained 1-aminomethylindan analogue (44) of mescaline (4) was recently designed [200] using the aforementioned in silico activated 5-HT 2A homology model. [137] Analogue 44 showed a threefold increase in affinity (K i = 130 nm), and a twofold increase in stimulating IP 3 accumulation (EC 50 = 6100 nm) compared to mescaline (4, K i = 360 nm; EC 50 = 11 300 nm).…”
mentioning
confidence: 99%